2018
DOI: 10.3390/ijerph15122889
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable Mortality-To-Incidence Ratio of Lung Cancer Is Associated with Health Care Disparity

Abstract: The mortality-to-incidence ratio (MIR) is associated with the clinical outcome of cancer treatment. For several cancers, countries with relatively good health care systems have favorable MIRs. However, the association between lung cancer MIR and health care expenditures or rankings has not been evaluated. We used linear regression to analyze the correlation between lung cancer MIRs and the total expenditures on health/gross domestic product (e/GDP) and the World Health Organization (WHO) rankings. We included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…This can be reflected by differences in MIRs. Globally, the MIR of lung cancer is 0.87 [21], while it is 0.19 for testicular cancer. Despite that, our study found a significant correlation between the MIR for testicular cancer and a country's WHO ranking, echoing the findings of previous papers on colon cancer and lung cancer [18,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be reflected by differences in MIRs. Globally, the MIR of lung cancer is 0.87 [21], while it is 0.19 for testicular cancer. Despite that, our study found a significant correlation between the MIR for testicular cancer and a country's WHO ranking, echoing the findings of previous papers on colon cancer and lung cancer [18,21].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the MIR of lung cancer is 0.87 [21], while it is 0.19 for testicular cancer. Despite that, our study found a significant correlation between the MIR for testicular cancer and a country's WHO ranking, echoing the findings of previous papers on colon cancer and lung cancer [18,21]. The association between the total expenditures on health/GDP and the crude rates of (A) incidence and (B) mortality, and the ASR (age-standardized rate) of (C) incidence and (D) mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QCI scores were calculated and scaled into 0 to 100 range, with higher scores representing better quality of care. Moreover, similar indices like mortality to incidence ratio were utilized to assess the quality of care in different cancers [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, lung cancer incidence in China has increased 465% over the past 30 years, ranking the highest among all cancer types since the beginning of this century, and accounting for more than one-third of global lung cancer mortality 37 . Gross domestic product (GDP) correlates negatively with case fatality, being estimated at 90% versus 74.8% in LMICs and HICs, respectively 38 . This phenomenon is multifactorial and likely associated with challenges in access to diagnostic tools leading to delayed detection, as well as barriers to adequate treatment 39 .…”
Section: Lung Cancer Risk Factors and Epidemiology In Lmicsmentioning
confidence: 99%